The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1016/j.ebiom.2021.103627
|View full text |Cite
|
Sign up to set email alerts
|

Lactate in the tumour microenvironment: From immune modulation to therapy

Abstract: Disordered metabolic states, which are characterised by hypoxia and elevated levels of metabolites, particularly lactate, contribute to the immunosuppression in the tumour microenvironment (TME). Excessive lactate secreted by metabolism-reprogrammed cancer cells regulates immune responses via causing extracellular acidification, acting as an energy source by shuttling between different cell populations, and inhibiting the mechanistic (previously 'mammalian') target of rapamycin (mTOR) pathway in immune cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
126
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(130 citation statements)
references
References 126 publications
4
126
0
Order By: Relevance
“…To survive, tumor cells must adapt to the harsh environments of nutrient stress and reduced pH and oxygen by increasing glucose uptake and lactate production; known as the Warburg effect (4). The increase in lactate production strongly supports diverse cancer cell activities, including cell proliferation, angiogenesis, and tumor invasion activity, promoting tumor aggressiveness (46,47). HIF-1 is a crucial element in the Warburg effect, which promotes disconnection of the TCA cycle from glycolysis and reductive glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…To survive, tumor cells must adapt to the harsh environments of nutrient stress and reduced pH and oxygen by increasing glucose uptake and lactate production; known as the Warburg effect (4). The increase in lactate production strongly supports diverse cancer cell activities, including cell proliferation, angiogenesis, and tumor invasion activity, promoting tumor aggressiveness (46,47). HIF-1 is a crucial element in the Warburg effect, which promotes disconnection of the TCA cycle from glycolysis and reductive glycolysis.…”
Section: Discussionmentioning
confidence: 99%
“…The CAA phenotype further associates with increased releases of metabolites such as lactate, pyruvate, free fatty acids, and ketone bodies [ 9 ]. Such adaptive metabolic state is believed to mimic the hypoxic status and to contribute to immunosuppressive events within the TME, in part through the upregulation of hypoxia-inducible factor-1α (HIF-1α) and c-Myc [ 10 , 11 , 12 ]. In terms of TME localization, these cells have been ascribed to the invasive front of human breast cancer tumors [ 6 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Especially in a tumor microenvironment (TME), altered glucose metabolism is characterized by enhanced lactate generation with a decrease in pH value and an increase in hypoxia [ 10 , 11 , 12 ]. Early studies of the immunosuppressive environment identified that extracellular lactate supports the generation of suppressive macrophages and regulatory T cells [ 13 , 14 ]. Further, lactate secretion is proton-coupled, leading to extracellular acidosis suppressing effector reduction [ 15 ].…”
Section: Introductionmentioning
confidence: 99%